Sosialisasi Tradisi Mappatabe’ Pada Pendidikan Karakter Anak Usia Dini Di Raudathul Athfal Perwanida Tokka Kabupaten Sinjai - A. Indri Wahyuni; Irwanti Said; Muh. Anwar (Universitas Islam Negeri Alauddin Makassar, 2024)
The research discusses the Socialization of the Mappatabe' Pada Tradition Early Childhood Education at Raudathul Athfal Perwanida Tokka for Minimizing Shifts in Civilization Values in Sinjai. The main problem in this research: 1. What are the factors causing the shift in civilization values in children at PAUD Raudathul Athfal Perwanida Tokka, Sinjai Regency?. 2. What is the socialization method for the Mappatabe tradition in PAUD RA Perwanida Tokka Sinjai Regency?. The type of research used is descriptive qualitative research which is located at PAUD Raudathul Athfal Perwanida Tokka, Alehanuae Village Sinjai Regency. The approach used is a sociological approach social transformation. There are 9 primary data sources, namely school principals, teachers teaching, 2 religious leaders, 2 youth leaders, and 3 parents of students while data secondary data obtained from digital books, research journals and other data sources can be used as complementary data. The data collection method applied is: observation, interviews, and documentation. Analysis of this research data through word reduction, data presentation and conclusion drawing. The results of this study indicate that the causal factors the shift in civilizational values in PAUD Raudathul Athfal Perwanida Tokka, namely: changing times, creating modern traditions. Technological development, increasingly sophisticated which makes individuals prefer a simple and simple life ignore cultural life. Lack of parental attention is very common occurs in children because there is no time to spend together. Method socialization of the Mappatabe' tradition at PAUD Raudathul Athfal Perwanida Tokka, namely: Primary socialization, socialization related to the family. Socialization Secondary, a level higher than primary, begins to adapt, is sensitive to school environment, playmates and the surrounding community. Socialization Tertiary, wider scope, world of work, new social world and are in the maturity phase.